2010
DOI: 10.1089/acm.2009.0321
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Brief and Sham Mindfulness Meditation on Mood and Cardiovascular Variables

Abstract: These results indicate that brief meditation training has beneficial effects on mood and cardiovascular variables that go beyond the demand characteristics of a sham meditation intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
223
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(244 citation statements)
references
References 24 publications
18
223
1
2
Order By: Relevance
“…awareness of breathing sensations) yet included verbal cues suggestive of meditative experiences. The study reported greater decreases in distressed mood and HR following the meditation condition compared to the sham condition (Zeidan et al, 2010). The present study extends this research by observing a stress phase prior to randomizing novice meditators to a mindfulness instruction or a mindfulness description condition.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…awareness of breathing sensations) yet included verbal cues suggestive of meditative experiences. The study reported greater decreases in distressed mood and HR following the meditation condition compared to the sham condition (Zeidan et al, 2010). The present study extends this research by observing a stress phase prior to randomizing novice meditators to a mindfulness instruction or a mindfulness description condition.…”
Section: Discussionsupporting
confidence: 59%
“…In a recent controlled experiment on mindfulness meditation that used cardiac measures, Zeidan et al (2010) studied 82 undergraduates with no meditation experience in a design comparing traditional meditation training with a sham condition. The sham condition lacked the essential instructions of mindfulness (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are only isolated studies, whose results seem to be in consonance with the meta-analysis of Sedlmeier et al (2012), in particular regarding the effect on the emotional variables and attentional processes (Tang et al, 2007;Zeidan, Johnson, Diamond, David, & Goolkasian, 2010;Zeidan, Johnson, Gordon, et al, 2010). Nevertheless, it is also possible to observe divergences among some of these findings.…”
mentioning
confidence: 84%
“…Although, in these reviews, the interventions are considered to be medium and long-term, with 30 days being the shortest duration analyzed, studies evaluating short-term training -such as that lasting a few days -have also found encouraging results (Creswell, Pacilio, Lindsay, & Brown, 2014;Ding, Tang, Tang, & Posner, 2014;Tang et al, 2007;Zeidan, Johnson, Gordon, & Goolkasian, 2010). It is worth emphasizing that there is no consensus in the literature in relation to the use of the terms "short-term" and "brief ", as these have been used for designating different quantities of practice, such as a single session of 10 minutes (Dickenson, Berkman, Arch, & Lieberman, 2012), five days (Tang et al, 2007), two weeks (Cavanagh et al, 2013), and experience of up to five years (Sukhsohale & Phatak, 2012).…”
mentioning
confidence: 99%